1993
DOI: 10.1177/002224379303000102
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Process Model of Service Quality: From Expectations to Behavioral Intentions

Abstract: Relying on a Bayesian-like framework, the authors develop a behavioral process model of perceived service quality. Perceptions of the dimensions of service quality are viewed to be a function of a customer's prior expectations of what will and what should transpire during a service encounter, as well as the customer's most recent contact with the service delivery system. These perceptions of quality dimensions form the basis for a person's overall quality perception, which in turn predicts the person's intende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
1,156
2
38

Year Published

1996
1996
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,930 publications
(1,244 citation statements)
references
References 18 publications
48
1,156
2
38
Order By: Relevance
“…A study by Boulding et al (1993) supports an assumption of this study in that service quality is relevant for customer loyalty in an educational context. Boulding et al (1993) report that the overall quality of an educational institution has a positive and significant impact on students' perceptions and attitudes, but they do not, however, provide deeper viewpoints into the structure or strength of the relationship between the quality and loyalty. In order to explore critical insights about the influence of perceived quality, this study decomposes perceived quality into two separate dimensions -namely, perceived QTS and QAS.…”
Section: My Retention and Loyaltysupporting
confidence: 81%
“…A study by Boulding et al (1993) supports an assumption of this study in that service quality is relevant for customer loyalty in an educational context. Boulding et al (1993) report that the overall quality of an educational institution has a positive and significant impact on students' perceptions and attitudes, but they do not, however, provide deeper viewpoints into the structure or strength of the relationship between the quality and loyalty. In order to explore critical insights about the influence of perceived quality, this study decomposes perceived quality into two separate dimensions -namely, perceived QTS and QAS.…”
Section: My Retention and Loyaltysupporting
confidence: 81%
“…Marketers need to better understand not only how expectations influence the overall evaluation but also understand at which stage(s) of this model are expectations most important. Research has identified various types of expectations (Boulding et al, 1993). The present study does not delineate between the various types, however, they may influence an evaluation differently; nor does the current study measure confirmation of expectations which has been shown to influence satisfaction formation (see Oliver, 1997).…”
Section: Theoretical Implicationsmentioning
confidence: 75%
“…Hence, confusion arises when researchers regard the use of both service quality and satisfaction in their models. In order to distinguish between service quality and satisfaction, Boulding et al (1993) indicated that service quality conceptualizes on an ''ideal'' or ''should'' expectation, while satisfaction concept is based on a ''desired'' or ''will'' expectation. Furthermore, emerging conceptual and operational definitions make the distinction clearer: service quality assessments emphasize the relatively specific dimensions, whereas satisfaction evaluations have a broader range of dimensions, and require customer experience (Oliver 1993;Parasuraman et al 1988).…”
Section: Service Quality-satisfaction-behavioral Intentions Paradigmmentioning
confidence: 99%